The Understanding of English Emotion Words by Chinese and Japanese Speakers of English as a Lingua Franca - Stine Mosekjær (Copenhagen Business School (CBS), 2016)
In this thesis I investigate the understanding and use of the English emotion words guilty, ashamed, and proud by Japanese and Chinese speakers of English as a lingua franca. By exploring empirical data I examine (1) how Japanese and Chinese participants understand and use the three stimulus words, (2) if their understanding and use differ from that of native English speakers, and (3) if so, what these differences are. In the thesis 65 participants are investigated. The participants consist of 20 native Japanese and 23 native Chinese. For comparison, a group of 22 British native English speakers is also investigated. The study is theoretically and conceptually founded in the literature of the interplay between language, culture, and thought, and draws on notions from the fields of cross-cultural semantics and emotions. As existing methods are not adequate for the purpose of the thesis, a new methodological framework is created. The design of the framework is based on features from existing methods used for testing language association, and methods for testing the universality of emotions and their expressions. Models for exploring cultural semantics are also used as inspiration. The framework, which is based on the theoretical notion of the word as an image-idea pair as suggested by the theory of linguistic supertypes, consists of three tests each addressing three different aspects of the understanding and use of the stimulus words: the Free Association test (FA test), the Context Bound Association test (CBA test), and the Picture Driven Association test (PDA test).
hdl:10398/9378
Keywords: 650